2016
DOI: 10.5543/tkda.2016.37806
|View full text |Cite
|
Sign up to set email alerts
|

Diagonal ear lobe crease is associated with increased epicardial adipose tissue and carotid intima media thickness in subjects free of clinical cardiovascular disease

Abstract: A significant and independent association between the presence of DELC and increased CIMT and EAT thickness was presently determined, for the first time, in subjects free of clinical cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…The detailed mechanisms of developing earlobe crease is uncertain, although it is speculated to be derived from loss or degeneration of elastic fibers by diminishing blood supply to the earlobes in a pathological study. Ziyrek et al [21] showed an association between the presence of diagonal earlobe crease and increased carotid intima-media thickness and epicardial adipose tissue thickness that the latter indicator can own strongly predict the severity of coronary artery disease. It also seems that the role of earlobe crease in the prediction of CAD can be augmented by the presence of other CAD risk factors such as hypertension and diabetes [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed mechanisms of developing earlobe crease is uncertain, although it is speculated to be derived from loss or degeneration of elastic fibers by diminishing blood supply to the earlobes in a pathological study. Ziyrek et al [21] showed an association between the presence of diagonal earlobe crease and increased carotid intima-media thickness and epicardial adipose tissue thickness that the latter indicator can own strongly predict the severity of coronary artery disease. It also seems that the role of earlobe crease in the prediction of CAD can be augmented by the presence of other CAD risk factors such as hypertension and diabetes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ziyrek et al [21] showed an association between the presence of diagonal earlobe crease and increased carotid intima-media thickness and epicardial adipose tissue thickness that the latter indicator can own strongly predict the severity of coronary artery disease. It also seems that the role of earlobe crease in the prediction of CAD can be augmented by the presence of other CAD risk factors such as hypertension and diabetes [21]. As shown by Kamal in 2017 [13], the effect of hypertension and diabetes on the presence of diagonal earlobe crease is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies trying to demonstrate an association between ELC and cIMT disclosed an apparent association between both variables [5, 6, 7, 8, 9]. However, the aforementioned studies were flawed by either biased selection of participants, a small sample size, limited assessment of the cIMT to a single artery wall, and different cutoffs used for defining an increased cIMT (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the ELC might be genetically determined, which might explain its different correlates with atherosclerosis according to race/ethnicity [4]. Information on the association between ELC and the carotid intima-media thickness (cIMT) – a surrogate of extracranial atherosclerosis – is limited [5, 6, 7, 8, 9]. Using the Atahualpa Project cohort, we aimed to assess this association in community-dwelling adults.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This simple clinical sign that can be easily observed and was fi rst described by Frank in routine clinical examination in 1973 ,who reported the signifi cant association of ELC with increased risk for coronary artery disease. [1][2][3][4][5] From that year forward, several studies have evaluated the potential link between ELC and coronary risk factors or coronary artery disease. 1,3,5 However, there is still uncertainty regarding the relevance of ELC to coronary atherosclerosis burden despite the notable number of studies available on this issue.…”
Section: Introductionmentioning
confidence: 99%